Semantiske neologismer - Martinsen, Bodil (HERMES - Journal of Language and Communication in Business, 1988)
Neologisms can, roughly speaking, be divided into formal and semantic neologisms. Focusing notably on the latter, the present paper adresses the question of how they are formed and suggests, based on Greimas' theory on the structuring of the meaning of the linguistic sign, that semantic neologisms are formed via a metaphoring process. This view challenges the traditional subdivision of semantic neologisms into metaphors, metonomy, generalization and specialization and topples the myth that the use of metaphors is exclusively a literary phenomen. Thus, metaphos are commonly used, e.g. in journalism.